Variations in Adipokine Genes AdipoQ, Lep, and LepR Are Associated with Risk for Obesity-Related Metabolic Disease: The Modulatory Role of Gene-Nutrient Interactions - Jennifer Emily Enns; Carla G. Taylor; Peter Zahradka (Journal of Obesity)
Obesity rates are rapidly increasing worldwide and facilitate the development of many related disease states, such as cardiovascular disease, the metabolic syndrome, type 2 diabetes mellitus, and various types of cancer. Variation in metabolically important genes can have a great impact on a population's susceptibility to becoming obese and/or developing related complications. The adipokines adiponectin and leptin, as well as the leptin receptor, are major players in the regulation of body energy homeostasis and fat storage. This paper summarizes the findings of single nucleotide polymorphisms in these three genes and their effect on obesity and metabolic disease risk. Additionally, studies of gene-nutrient interactions involving adiponectin, leptin, and the leptin receptor are highlighted to emphasize the critical role of diet in susceptible populations.